(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: Optimal glycaemic control in type 2 diabetics is of utmost importance in preventing the complications of diabetes which lead to increased morbidity and mortality related to the disease. Some studies have shown that vitamin D deficiency was prevalent in type 2 diabetic patients and was associated with poor glycaemic control. This study aimed to determine the vitamin D3 levels in type 2 diabetic patients and its association with glycaemic control. Patients and methods: This cross sectional study was carried out in the outdoor department of Medical Unit II of Sir Ganga Ram Hospital/Fatima Jinnah Medical University Lahore from Feb 10, 2019 to May 9, 2019. A total of 45 cases of type 2 diabetes mellitus were enrolled in this study after taking informed consent from them. Demographic details (name, age, gender, including duration of diabetes) were obtained and blood sample were taken for HbA1c and 25-OH vitamin D3 levels. Vitamin D deficiency was diagnosed by taking serum level <20 ng/mL as cut off. The data analysis was carried out in SPSS version 20. Quantitative variables like age and duration of diabetics were taken as mean and standard deviation. Qualitative variables, gender and vitamin D3 levels and HbA1c levels were taken as percentage. Post stratification chi-square test was applied taking p-value <0.05 as significant. Results: Out of 45 patients, 17 (37.78%) were male and 28 (62.2%) were female. Mean age was 49.56 ± 10.77 years. Mean duration of diabetes was 5.91 ± 3.74 years. Mean vitamin D levels were 36.36±17.9 ng/ml. Out of 45 patients, 7 (15.6%) were found deficient, 10 (22.2%) insufficient, 27 (60%) sufficient and 1 (2.2%) had vitamin D toxicity. Among the patients with sufficient vitamin D levels, 12 (44.4%) were male and 15 (55.5%) were female. Two (16.6%) male patients with sufficient vitamin D levels had good glycemic control as compared to none of the female patients. Two (16.6%) male and 2 (13.3%) female patients with sufficient vitamin D had fair HbA1c. Most of the patients had poor control of HbA1c despite sufficient vitamin D levels including 8 (66.6%) males and 13 (86.6%) females. Mean HbA1c concentration was 9.3±1.66%. Out of 45 patients, 2 (4.4%) had good glycaemic control, 5 (11.11%) had fair and 38 (84.4%) had poor control. It was seen that out of 7 vitamin D deficient, 6 (85.7%) had poor glycemic control, 1 (14.3%) had fair and none had good glycaemic control. The post stratification chi-square test was applied to determine the significant association between vitamin D levels and HbA1c and showed a p-value of 0.196 which is statistically insignificant. The Pearson correlation revealed a value of -0.012 which shows a negative correlation between vitamin D and HbA1c levels. Conclusions: No statistical significance could be established between vitamin D deficiency and poor glycemic control. There is a weak negative correlation between vitamin D and HbA1c levels showing that low Vitamin D levels are associated with higher HbA1c concentration.